2018
DOI: 10.17576/jsm-2018-4701-06
|View full text |Cite
|
Sign up to set email alerts
|

Boron Application in Clay-Loam Soil for Improved Growth, Yield and Protein Contents of Mungbean in Water-Stresses

Abstract: Boron is considered important to improve the drought resistance, yield and protein contents of pulses. Two years of field experiment was conducted to evaluate the effect of boron application and water stress given at vegetative and flowering stages on growth, yield and protein contents of mungbean during spring 2014 and 2015. The experiment was laid out in randomized complete block design with split-plot arrangement giving more emphasis to boron. The experiment comprised three water stress levels (normal irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
6
6
0
1
Order By: Relevance
“…Similarly, the lowest 1000-seed weight (21.11 g) was obtained from B 0 (control). Maqbool et al (2018) and Vimalan et al (2017) also noted similar results. Weight of 1000-seed was significantly influenced by the interaction effect of different levels of irrigation and boron application (Table 4).…”
Section: -Seed Weightsupporting
confidence: 52%
“…Similarly, the lowest 1000-seed weight (21.11 g) was obtained from B 0 (control). Maqbool et al (2018) and Vimalan et al (2017) also noted similar results. Weight of 1000-seed was significantly influenced by the interaction effect of different levels of irrigation and boron application (Table 4).…”
Section: -Seed Weightsupporting
confidence: 52%
“…However, Karmakar et al (2015) noted that Zn significantly influenced to attain maximum pods of mungbean. Maqbool et al (2018) reported that yield attributes of mungbean responded to B in soil application when B availability is lower. Combined micronutrients (Zn, B and Mo) might be assisted in better utilization of the major nutrients (NPK) which contributed to increase the pods per plant and seeds per pod and ultimately produced the higher productivity.…”
Section: Growth and Yield Attributes Of Mungbeanmentioning
confidence: 99%
“…Results showed that the highest days to flower (37.17 days) was recorded with F0 (Recommended dose) fertilizer dose which was statistically at par with F1 (R+ Additional 10 kg K ha -1 + 1 kg B ha -1 ) and the lowest days to flower (29.83 days) with F3 (R+ Additional 10 kg K ha -1 + 2 kg B ha -1 ) which was statistically similar with F2 ( R+ Additional 20 kg K ha -1 + 1 kg B ha -1 ) fertilizer dose. Maqbool et al [29] also found that B had significant influence on flowering habit of mungbean.…”
Section: Days To Flowermentioning
confidence: 93%